Contaminated land assessment and remediation technologies: Hong Kong and US practices - Lo, I.M.C. (Progress in Nutrition, 2011)
Summary The risk assessment is the core of the contaminated land investigation and assessment process. The main objective of investigations is to obtain information on sources, pathways and receptors present on or adjacent to a site. The presence of a linkage between these may then constitute a risk, the significance of which must be assessed and is dependent on many factors. In this paper, the fundamental principles and techniques of risk assessment as applied to contaminated land assessment and remediation are discussed. In Hong Kong, the RBRGs have been established in 2007 to protect the health of people who may potentially be exposed to land contaminated by chemicals. The RBRGs were developed for four different post-restoration land-use scenarios. They are intended to be used as site assessment criteria that are appropriate on a stand-alone basis for the majority of sites in Hong Kong, where human health is the only significant receptor that needs to be protected. This new regulatory guideline and the Dutch B levels of the Netherlands are compared and discussed. In addition, the remediation technologies applied for the former Kai Tak Airport are also highlighted. Tecnologie di valutazione e bonifica di terreni contaminati: le procedure a Hong Kong e degli Stati Uniti Riassunto La valutazione del rischio è il cuore delle indagini e delle procedure di valutazione di terreni contaminati. Il principale obiettivo delle indagini è quello di ottenere informazioni sulle origini, i percorsi e i recettori presenti o adiacenti ad un sito. La presenza di un collegamento tra questi può poi costituire un rischio, il cui significato deve essere valutato e dipende da molti fattori. In questo lavoro sono discussi i principi fondamentali e le tecniche di valutazione del rischio applicate alla valutazione e bonifica di terreni contaminati. A Hong Kong, sono stati istituiti nel 2007 gli RBRGs per tutelare la salute delle persone che possono potenzialmente essere esposte a terreni contaminati da sostanze chimiche. Gli RBRGs sono stati sviluppati per quattro diversi scenari post-ripristino di utilizzo del territorio. Essi sono destinati ad essere utilizzati come criteri di valutazione del sito appropriati su una base indipendente per la maggior parte dei siti a Hong Kong, dove la salute umana è l’unico recettore significativo che deve essere protetto. Questi nuovi orientamenti normativi vengono confrontati e discussi con i livelli Dutch B dell’Olanda. Inoltre, sono anche evidenziate le tecnologie di bonifica applicate per l’ex aeroporto di Kai Tak.